E-learning effectiveness in developing scientific research skills among high school students in the Kingdom of Saudi Arabia - Al-Ghamdi, Eman Embark Abdullah; Qutb, Iman Muhammad Mabrouk (Journal of Educational and Psychological Sciences, 2020)
The study aimed to measure the effectiveness of e-learning in developing scientific research skills for high female school students in the kingdom of Saudi Arabia, the study relied on the semi-experimental Method in order to reveal the effectiveness of the independent variable (e-learning) on ​​the dependent variable which is (the development of scientific research skills), the study population consisted of secondary school students in the kingdom of Saudi Arabia in the academic year 1439 ah, in the second secondary class of the twenty-fourth secondary school for girls in Dammam, and the second secondary school for girls in Dammam, as the individuals of the sample were randomly chosen, and the number of female students for whom the study was applied was (72) female students, they were divided into two groups, one is experimental and the other is a control, and the experimental group consisted of (36) female students, using e-learning program, while the control group consisted of (36) female students, using traditional learning, the study tools have been built, which are: an achievement test, a note card, and ensuring the validity and reliability of the tools, The researcher reached through the study that there is a statistically significant difference at the level (0.05) between the average scores of female students of the experimental group that use (e-learning) and the average score of female students of the control group that use (traditional learning) in the post-application of the achievement test and the observation card for scientific research skills in favor of the experimental group, The researcher recommended it through the study the need to take advantage of e-learning to teach various performance concepts and skills for high school female students.
Keywords: e-learning; scientific research skills; high school female students